Autonomous Safety Mechanism for Building: Fire Fighter Robot with Localized Fire Extinguisher - Yahaya, Izyan (International Journal of Integrated Engineering, 2020)
With advent of robotics technology in the modern days, the use of fire bucket to put up a small fire is seen as outdated. The autonomous approach (by using robots) in safe guarding the human environment building from potential hazard such as fire is deemed necessary. Big fire can be prevented by detecting small fire as quickly as possible. Fire detection device in a building needs to be reliable and effective. Autonomous system can be leveraged to accomplish the hazard detection without human supervision. Moreover, if the hazard eradication follows the detection in an autonomous mode, the solution has a profound impact to the safety of a building. A conceptual Fire Fighter Robot prototype is proposed in this paper. The dynamic model of the conceptual robot is derived. The control system based on nonlinear feedback control is designed to control the movement of the robot when dispersing the sand to put out the fire source. The designed autonomous system detects small flame in a confined area and put it out before it turns to big fire and spreads. A microcontroller, forming the brain of the robot, is coded with a supervisory control algorithm integrated with flame sensor modules are used for the detection of flame. The robot scans the room from front to back and vice versa. When flame is detected, the robot is deployed to directly above the flame source. Sand is used to extinguish the flame by targeting precise location of flame source. At the same time, the alarm will ring and send the message to the owner via Wi-Fi. The robot is capable of extinguishing fire from chemical substances and petrol. Sensitivity of flame sensors at different environment with different brightness is tested through analog reading of the serial monitor.